Colaboradores - Geraldello, Camilla Silva (Faculdade de Filosofia e Ciências, 2019)
Biografias e emails dos colaboradores desta edição:   Ada Celsa Cabrera García Arturo Noel Noyola Muñoz Bruno Maciel Santos Gabriel Siracusa Gilberto Maringoni Jackson Silva Ribeiro Mariana Balau Silveira Mariana Morena Pereira Mike Omilusi  Renan Holanda Montenegro